PENGELOMPOKAN STUNTING MENGGUNAKAN METODE K-MEDOIDS DI DAERAH ISTIMEWA YOGYAKARTA (DIY) - Cahyani, Amalia Rizki; Muhajir, Muhammad; Puspita, Ersa Riga; Pratiwi, Lathifah Aliya (MAp (Mathematics and Applications) Journal, 2024)
Stunting, or the condition of short stature in toddlers, is a problem caused by prolonged insufficient nutrition intake. This issue arises from inadequate feeding practices that do not meet the nutritional needs of a toddler. Stunting can begin during fetal development and becomes apparent around the age of two. Several factors contribute to stunting, including high-risk levels, lack of adequate housing, lack of proper sanitation facilities, lack of access to safe drinking water, and inadequate family income. This study employs k-medoids cluster analysis to identify the grouping of sub-districts in the Yogyakarta Special Region (DIY Province) based on stunting risk factors. The research findings indicate that Cluster 1 has the highest rates of stunting and lack of family income, Cluster 4 has the highest instances of inadequate access to safe drinking water and housing, and Cluster 5 has the highest rates of inadequate sanitation facilities.